The control of a back-to-back power converter for small-scale reluctance synchronous generators in grid-connectedwind turbine systems - Mitchell, Joshua Cole (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScEng)--Stellenbosch University, 2017.